Acknowledgment to Reviewers of Brain Sciences in 2020 - Brain Sciences Editorial Office (Brain Sciences, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Brain Sciences maintains its standards for the high quality of its published papers [...]